Blakea cubarralensis (Melastomataceae: Pyxidantheae): a new species from Colombia - Urrea, Johan; Mendoza-Cifuentes, Humberto; García, Néstor; Rojas, Lyndon Carvajal (Phytotaxa, 2024)
A new species of Blakea (Melastomataceae) from the department of Meta, Colombia is described and illustrated here, with comments on its etymology, distribution and habitat, phenology, conservation status and taxonomic affinities. Blakea cubarralensis sp. nov. is readily distinguished by its floral bracteoles that are longer than the calyx lobes, the outer pair ovate-elliptic with a long-acuminate apex and 3-nerved, the lobed calyx, the anther connective prolonged into a blunt knob and the ovary 12-locular. The new species is categorized as Endangered (EN) according to the IUCN Red List. This novelty highlights the importance of sub-andean forests and the need to conserve and increase botanical explorations in them.